2006
DOI: 10.1093/sw/51.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking Behaviors and Depression among African American Adolescent Boys

Abstract: This study examined the help-seeking behaviors of depressed, African American adolescents. Qualitative interviews were conducted with 18 urban, African American boys, ages 14 to 18, who were recruited from community-based mental health centers and after-school programs for youths. Interviews covered sociodemographic information, questions regarding depressive symptomotology, and open-ended questions derived from the Network-Episode Model--including knowledge, attitudes and behaviors related to problem recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
124
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(136 citation statements)
references
References 25 publications
9
124
0
3
Order By: Relevance
“…This socialization is often reinforced by "macho messages" delivered by peers that the expression of feelings and emotions is unmanly (BoydFranklin, Franklin, & Toussaint, 2000,p.229). The fear of being labeled "crazy" or being called "soft" is likely to constrain the expression of a range of emotions by Black males in family, school, and community contexts (Lindsey et al, 2006). It cannot be diminished, however, that the repression of certain feelings and emotions that might signal vulnerability serves a legitimate function in the community and neighborhood contexts that many Black males reside and must daily navigate.…”
Section: Discussionmentioning
confidence: 99%
“…This socialization is often reinforced by "macho messages" delivered by peers that the expression of feelings and emotions is unmanly (BoydFranklin, Franklin, & Toussaint, 2000,p.229). The fear of being labeled "crazy" or being called "soft" is likely to constrain the expression of a range of emotions by Black males in family, school, and community contexts (Lindsey et al, 2006). It cannot be diminished, however, that the repression of certain feelings and emotions that might signal vulnerability serves a legitimate function in the community and neighborhood contexts that many Black males reside and must daily navigate.…”
Section: Discussionmentioning
confidence: 99%
“…Family, close friends, and partners are all identified by adolescents as individuals to whom they would disclose emotional problems and mental health concerns (Booth et al 2004;Burns and Rapee 2006;Ciarrochi et al 2003;Gilchrist and Sullivan 2006;). Help-seeking preferences can vary with age (Tishby et al 2001), sex (Lindsey et al 2006), or by ethnicity (O'Donnell et al 2003). Some minority adolescents identify family as a source of help to a lesser extent.…”
Section: Preferred Sources Of Helpmentioning
confidence: 99%
“…Beliefs that seeking help is a sign of weakness, or character weakness (Lindsey et al 2006;Vanheusden et al 2008), and that counseling should be the last resort are reported by young people. Strong negative emotions also influence a young person's willingness to seek help.…”
Section: Beliefs About Help-seeking Symptoms and Treatmentmentioning
confidence: 99%
“…Estes dados demonstram que a avaliação do suporte instrumental recebido pelos jovens está de facto relacionada com a procura dos cuidados de saúde, conforme sugerido na literatura (Lindsey et al, 2006). Para além disso, os resultados evidenciam que a percepção de acessibilidade temporal é maior para aqueles que mais recorrem aos serviços.…”
Section: Discussão Dos Resultadosunclassified
“…Os estudos que abordam o acesso aos cuidados de saúde indicam que os padrões de recorrência podem ser moderados pelo tipo de problemas experienciados e o suporte social oriundo dos membros da rede. As redes de suporte social podem providenciar cuidados ou consistir em recursos para a identificação de fontes formais de suporte, pelo que a recorrência aos serviços de saúde pode estar relacionada com a quantidade e qualidade do suporte social institucional recebido (Lindsey et al, 2006).…”
unclassified